Non-Epitheliotropic Cutaneous Lymphoma with Systemic Dissemination in a Dog - Rosseto, Laís Guedes; Pitol, Beatriz Crepaldi Aléssio; Andreussi, Paulo Antonio Terrabuio; Palumbo, Mariana Isa Poci; Ventura, Adriana; Babo-Terra, Veronica Jorge (Acta Scientiae Veterinariae, 2021)
Background: Cutaneous lymphoma is a highly malignant neoplasm, which can originate in the epidermis or dermis, as well as be disseminated to other organs such as lung, heart, arm, liver and bone marrow. It comes in the form of nodes of various sizes, erythematous and alopecic, itching may or may not occur. The diagnosis is made by cytological and histopathological examination of the compromised tissue. However, it is important to perform complementary tests for clinical staging and prognostic characterization. The objective is to report a case of non-epitheliotropic cutaneous lymphoma with systemic dissemination in a dog. Case: A female mixed bred adult canine was attended at the Veterinary Hospital of the Federal University of Mato Grosso do Sul with a history of progressive weight loss and the presence of alopecic and non-pruritic subcutaneous nodules in the torso, nasal plane and pelvic limbs, starting 4 months ago. After approximately 20 days, the presence of rapidly evolving ulcerated nodules was noted. On physical examination, generalized lymphadenomegaly was observed and among the dermatological findings were multiple nodules of varying sizes with the presence of ulceration in the center of the lesions, alopecia, erythema and raised edges, in the region of the nasal sinus, pelvic and thoracic limbs, tail, thoracolumbar and abdominal region. The animal also presented right pelvic limb edema with painful sensibility to manipulation CBC and biochemical tests (albumin, alanine aminotransferase, creatinine, urea, alkaline phosphatase, globulins, total proteins and fractions) were performed, being observed as normocytic normochromic type anemia alteration (erythrocytes: 2.78 106/µL; hemoglobin: 6.8 g/µL; globular volume: 18.8%), leukopenia (4,000/mm³) with presence of metamyelocytes (120/mm³) and rods (1,080/mm³) and lymphopenia (80/mm³). Three samples of the nodules were collected for histopathological examination and a definitive diagnosis of cutaneous lymphoma was obtained. The material was then submitted to immunohistochemical examination, which showed that it was a non-epitheliotropic cutaneous lymphoma of T immunophenotype. Due to the compromised quality of life and unfavorable prognosis, the owner opted for euthanasia of the animal. In the necropsy examination, lymph nodes, subcutaneous tissue, skeletal muscle, heart, pericardial sac, tongue and multifocal infiltrate of neoplastic cells were observed, findings suggestive of multicentric lymphoma or infiltrations by dissemination of cutaneous lymphoma. Discussion: Non-epitheliotropic skin lymphomas exhibit rapid progression and infiltration into lymph nodes and subsequent systemic involvement. The diagnosis is based on clinical-dermatological signs, fine needle cytology, histopathological and immunohistochemical examination. Normocytic normochromic anemia is the most observed alteration in patients with lymphoma, followed by leukocytosis, leukopenia, thrombocytopenia, neutrophilia and leukoerythroblastic reactions. Dogs with T-cell lymphoma have a worse prognosis for life span and disease-free intervals than those with B-cell lymphoma, so immunophenotyping is critical to determine prognosis. In the present report, histopathological and immunohistochemical examinations were decisive for the diagnosis of the present report, because the expression CD3 and the negativity for CD79a proved that the neoplasm is of T lymphocyte lineage. The definitive diagnosis was obtained by histopathology, however, immunohistochemistry determined the immunophenotype of the neoplasia as non-epitheliotropic T lymphocyte.